Collaborative Writing in a Third Language: How Writers Use and View Their Plurilingual Repertoire During Collaborative Writing Tasks - Payant, Caroline; Maatouk, Zeina (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
Recent years have witnessed major development in plurilingual pedagogies which support the use of learners’ repertoire of languages in language learning contexts (Payant & Galante, 2022; Piccardo, 2013).  However, little research has been undertaken to examine adult plurilingual learners’ perceptions towards the use of their languages during authentic collaborative writing tasks and contrasted these views with their actual behaviours.  In this case study, six plurilingual adult learners of English in a Canadian university with three unique L1s (Romanian, Russian, Spanish) completed two collaborative writing tasks on two separate occasions.  Each dyad shared the same linguistic profiles and were encouraged to draw on their entire repertoire to complete the tasks.  Semi-structured interview data shows differing levels of openness towards L1 and L2 (French) use during language-learning writing tasks.  The analysis of the interaction confirms multiple uses for the L1; however, the L2 was seldom observed during interactions.  The findings are discussed from a plurilingual lens and pedagogical implications are discussed.